PEMBELAJARAN QIRᾹAT AL KUTUB DI PONDOK PESANTREN AL-HUDA TINJAUAN KURIKULUM, BAHAN AJAR DAN METODE - Amal, Adi Ihsanul; Isnaini, Rohmatun Lukluk (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Islamic boarding schools are known as religious educational institutions and religious problems. In modern times, Al-Huda Islamic Boarding School still applies traditional learning systems such as Qirāatul Al-Pole learning. The development of Islamic boarding school education is inseparable from the existence of a curriculum that is used as a reference in the implementation of education and plays an active role in achieving the educational goals of Islamic boarding schools, as well as teaching materials and methods. So, the purpose of this research is to find out the curriculum, teaching materials, and learning methods of the yellow book at the Al-Huda Islamic Boarding School. This research method uses descriptive qualitative methods, with data collection techniques by interviews, observation, and documentation. The results of this study indicate that the Al-Huda Islamic boarding school in learning qirāatul al-polar uses a curriculum related to nahwu, sharf, and balaghah, the teaching materials used are basic books such as the safinah and tijan books using the sorogan method. Not a few students often take part in Musabqoh qiraatul al-pole (MQK) competitions at the sub-district to national levels and often win prizes.